Evaluation of a Recirculating Aquaculture System Research Facility Designed to Address Current Knowledge Needs in Atlantic Salmon Production - Mota, Vasco C.; Striberny, Anja; Verstege, Gerhardus C.; Difford, Gareth F.; Lazado, Carlo C. (Frontiers in Animal Science, 2022)
A better understanding of recirculating aquaculture system (RAS) biosecurity is crucial for the sustainable and ethical production of Atlantic salmon smolt and post-smolt in these systems. This study described and evaluated the performance of a RAS facility for fish infection research with Atlantic salmon as the main animal model. Fish body weight, length, water quality, and system metrics from five independent experimental trials conducted between September 2020 and July 2021 were used to analyze the variation within and between treatments. Statistical power analysis was performed to determine the minimum number of fish required. The fish parameters variability showed that the inter-class correlation coefficient was on average low (0.1) and that the variation within tanks was larger than the variation between the tanks. The power analysis showed that 15 fish were required to be sampled per tank under these study conditions. Variation of water quality and system management metrics among the five experimental trials was higher compared to the variation within the five experimental trials. Moreover, the variation of the water quality parameters controlled by sensors was relatively low, whereas the parameters depending on biofilter maturation level and performance presented a very high variation. Water exchange rate-dependent quality parameters showed a similar variation value, i.e., nitrate and water turbidity. The established baseline for variability and performance presents an important reference for the design and realization of future experiments in RAS facilities. It is foreseen that the current research facility will develop new knowledge to improve the RAS biosecurity in the Atlantic salmon aquaculture industry.